Language and communication in mental retardation - Abbeduto, Leonard, 1954- (International review of research in mental retardation, 2003)
Language and communication problems have long figured prominently in the definition of mental retardation. Volume 27 of the International Review of Research in Mental Retardation focuses exclusively on these language and communication issues. The pace of research on language learning and use in mental retardation has increased in recent years and taken new direction. This revitalization has been fueled by three factors: 1) advances in genetic technologies allowing investigation of the behavioral phenotypes of well-defined syndromes, 2) an increased emphasis on maximizing abilities of individuals with mental retardation to live and succeed in a broader range of contexts and settings, and 3) theoretical debates concerning the mechanisms of language development and the nature of the human mind. Contents in Language and Communication in Mental Retardation include syndromes (e.g., Down syndrome, Williams syndrome), domains of language skill (e.g., reading), and intervention strategies. Contains the most current research on genetic syndromes, including Williams syndrome, Down syndrome, and fragile X syndrome. Outlines the most current research on language and communication intervention for persons with mental retardation. Authors consider the implications of the research reviewed for both theory and clinical practice. Authors bring state-of-the-art knowledge of cognitive science, developmental science, linguistic, and behavioral genetics to bear on important questions about language and mental retardation. Includes new research on long-studied conditions (e.g., Down syndrome) and disorders that are of only recent interest to child language researchers (e.g., fetal alcohol syndrome). Includes a consideration of nonverbal, as well as verbal, communication.